The Influence of Formation Culture, Organization and Job Satisfaction to Commitment of Education Personnel At New College - Wijaya, Acum; Supriyanto; Nofitasari, Susi (Universitas Indonesia Mandiri, 2026)
This study aims to examine the influence of organizational culture and job satisfaction on organizational commitment among educational staff at newly established private higher education institutions. Newly founded universities face challenges in developing a strong organizational culture while simultaneously maintaining job satisfaction to foster long-term employee commitment. This research employed a quantitative approach using a survey design. The population consisted of all educational staff at a private university in South Lampung Regency that has been established for less than five years. A total of 35 respondents were selected using a saturated sampling technique. Data were collected through a Likert-scale questionnaire and analyzed using multiple linear regression analysis. The results reveal that job satisfaction has a positive and significant effect on organizational commitment when tested partially. In contrast, organizational culture does not have a significant partial effect on organizational commitment. However, simultaneous testing indicates that organizational culture and job satisfaction together have a positive and significant influence on organizational commitment. These findings suggest that in newly established higher education institutions, job satisfaction plays a dominant role in shaping the commitment of educational staff, while organizational culture requires time to be fully internalized. This study recommends that new universities prioritize policies aimed at improving job satisfaction and continuously strengthening the internalization of organizational culture to enhance organizational commitment among educational staff.